2014
DOI: 10.1007/s13277-014-1605-x
|View full text |Cite
|
Sign up to set email alerts
|

CXCL5 as a potential novel prognostic factor in early stage non-small cell lung cancer: results of a study of expression levels of 23 genes

Abstract: As the current staging system is imprecise for estimating prognosis of early stage non-small cell lung cancer (NSCLC), it is important to identify other methods for selecting high-risk patients after failed surgical treatment. The aim of the study was to evaluate the expression of 23 genes as putative prognostic markers in early stage NSCLC. The study was performed on 109 pairs of tumor and matched unaffected lung tissue surgical specimens taken from stage I and II NSCLC patients. We evaluated the mRNA level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…The correlation of I-MDSC with IL-8 and CXCL5 is especially interesting, given that little is known about the factors that draw I-MDSC into the tumor parenchyma. Interestingly, CXCL5 expression has been associated with decreased survival in a number of human tumors (55), and IL-8 levels were recently shown to correlate with PFS and OS in mRCC (54) (for CXCL-5, these were studies on tumor parenchyma, whereas with IL-8 this was a study on circulating protein).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of I-MDSC with IL-8 and CXCL5 is especially interesting, given that little is known about the factors that draw I-MDSC into the tumor parenchyma. Interestingly, CXCL5 expression has been associated with decreased survival in a number of human tumors (55), and IL-8 levels were recently shown to correlate with PFS and OS in mRCC (54) (for CXCL-5, these were studies on tumor parenchyma, whereas with IL-8 this was a study on circulating protein).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high expression of CXCL5 predicts worse prognosis for both RFS and OS. In deed, recent studies analyzed the effect of 18 out of the 23 differently expressed genes between the tumor and normal tissues on overall survival, only CXCL5 had significantly influence on overall and disease-free survival [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Metodieva et al also showed a high expression level of CXCL9 in 12 NSCLC patients [37]. However, a study by Kowalczuk et al also showed that CXCL9 expression was low in 109 NSCLC tumor tissues, but it could not influence both overall and disease-free survival [38]. In addition, other studies have also demonstrated that Egr-1 deficiency [22], IL-7 [39], CCL21 [40], and myeloid-derived suppressor cells depletion [41] reduced tumor burden by upregulating CXCL9 and CXCL10 expression, which played an anti-angiogenic role and attracted tumor macrophages, CD4 and CD8+ T lymphocytes, and NK cells.…”
Section: Lung Cancermentioning
confidence: 98%